R&D and the Incentives from Merger and Acquisition Activity - Phillips, Gordon M.; Zhdanov, Alexei (Review of Financial Studies, 2013)
[We provide a model and empirical tests showing how an active acquisition market affects firm incentives to innovate and conduct R&D. Our model shows that small firms optimally may decide to innovate more when they can sell out to larger firms. Large firms may find it disadvantageous to engage in an "R&D race" with small firms, as they can obtain access to innovation through acquisition. Our model and evidence also show that the R&D responsiveness of firms increases with demand, competition, and industry merger and acquisition activity. All of these effects are stronger for smaller firms than for larger firms.]